New efficient synthesis of 1H-imidazo-[4, 5-c]quinolines by a sequential Van Leusen/Staudinger/aza-Wittig/carbodiimide-mediated cyclization. Issue 50 (13th December 2018) - Guan, Zhi-Rong; Liu, Zi-Ming; Ding, Ming-Wu
Abstract: A new efficient synthesis of multisubstituted 1 H -imidazo-[4, 5- c ]quinoline derivatives via sequential van Leusen/Staudinger/aza-Wittig/carbodiimide-mediated cyclization was developed. Azides4, obtained from Van Leusen reaction of 2-azidobenzaldehyde1, amine2 and TosMIC (tosylmethyl isocyanide)3, reacted with triphenyl phosphine to produce iminophosphorane5 . A tandem aza-Wittig reaction of iminophosphorane5 with isocyanate generated 1 H -imidazo-[4, 5- c ]quinoline7 through carbodiimide intermediate6 in moderate to good yield. Graphical abstract: